Ambient Assisted Living 2014
DOI: 10.1007/978-3-319-01119-6_1
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Sensor for Real-Time Monitoring of Indoor Thermal Comfort for Ambient Assisted Living

Abstract: The present paper illustrates an innovative low cost solution for the monitoring of indoor thermal comfort by means of Predictive Mean Vote (PMV ) index for multiple positions. This is particularly interesting in an Ambient Assisted Living environment as replacement of typical thermostat used for the climate control. In fact, the system proposed considers also personal parameters, as metabolic rate (M) and clothing level (I cl ), instead of the merely environmental parameters. If this is important for normal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Among the parameters affecting indoor thermal comfort, this physiological parameter is one of the most important. In Revel et al (2014b) a sensitivity analysis of the PMV index was performed to investigate the PMV variation due to the metabolic rate. The authors report that the metabolic rate has a high influence, which increases especially for lower values (<1met).…”
Section: Calibration Curves For the Real-time Measurement Of Metabolimentioning
confidence: 99%
“…Among the parameters affecting indoor thermal comfort, this physiological parameter is one of the most important. In Revel et al (2014b) a sensitivity analysis of the PMV index was performed to investigate the PMV variation due to the metabolic rate. The authors report that the metabolic rate has a high influence, which increases especially for lower values (<1met).…”
Section: Calibration Curves For the Real-time Measurement Of Metabolimentioning
confidence: 99%
“…This setting is even more complex to be used for trucking patients. Actually most of the other studies and systems that we found in the literature are designed for monitoring dementia patient for indoor activities [5,6,7]. These technologies are very complex to be used for monitor the outdoor patients activities.…”
Section: Related Research Workmentioning
confidence: 99%
“…With the sensing data, real-time visualization platforms for indoor environments were developed, which aimed to provide the building manager with a more efficient decisionmaking process. For example, Revel et al (2014) developed a low-cost thermal comfort monitoring system by means of the predicted mean vote (PMV) index of multiple positions calculated through the collected environmental parameters such as temperature, relative humidity, and air velocity. Chang et al (2018) presented a framework to achieve colorful visualization of indoor temperature and humidity associated with adaptive thermal comfort values, which used Dynamo to import real-time sensing data into Autodesk Revit through the Arduino microcontroller.…”
Section: Introductionmentioning
confidence: 99%